SIGNIFICANCE OF CONSUMER CULTURE AND LIFESTYLE FOR CONSUMPTION OF READY MEALS - arora, shweta (2006)
Ready meals are fully cooked and ready to eat with a shelf life that ranges from few months to 3 years. They are one of the fastest growing areas of the food market in both developed and developing countries. A demand of ready meals is growing continuously everywhere including U.K. Especially the popularity of Indian dishes, chicken tikka masala etc. provides most of the inspiration for the ready meals that form the bulk of the retail market, as well as for cooking sauces. Though the demand for the ready meals is increasing in the global market, the supply is still not satisfactory. For example, there are more than 500 units in London, which are into ready meals. This shows that exports as well as the domestic market offer a vast scope for the Indian producers to excel in this sector. The Indian meal sector in U.K. is being challenged by other cuisines, which will probably show faster growth. Therefore, Indian suppliers will have to meet the needs and demands of various types of consumer, by providing some with new dishes and to others with the familiar preferred ready meals. The ethnic food market also continues to grow in U.K. as consumers demand more diverse flavors as a result of travel and the abundance of ethnic restaurants. To quote an example: Waitrose collaborated with renowned London Indian restaurant Quilon to launch a new range of ready meals to compete with Sainsbury's Bombay Brasserie range. Thus, as there is a great potential for the packaged ready meals, the main relevance of conducting this research is to study the changing U.K. consumers' attitude and behavior towards ready meals and measure the growth opportunities by evaluating the various factors leading to their growth. The research will be helpful in understanding the consumers' preferences and perceptions with regard to ready meals as home meal replacement. The result of the study will also provide the companies dealing in Ready meals as to what consumers actually want and what changes suggested by consumers, if adopted seriously, can help in gaining a competitive edge on its competitors. Through this research it is possible to know whether ready meals is actually a convenient substitute to home fresh cooked meals or the manufactures are producing it for the profit motive and ignoring the health of their consumers. The study indicates that the strategy of the marketer in ready meals is to inform and educate consumers regarding the absence of preservatives in their food, price reduction keeping quality intact and increasing variety of ready meals along with increasing the quantity for different cuisines.